The structural characterization and UV-protective properties of an exopolysaccharide from a Paenibacillus isolate - Xu, Xiaodong; Ding, Zhao; Pu, Chunlin; Kong, Changchang; Chen, Shijunyin; Lu, Weiling; Zhang, Jianfa (Frontiers in Pharmacology, 2024)
Introduction Overexposure to ultraviolet (UV) light is known to cause damage to the skin, leading to sunburn and photo-aging. Chemical sunscreen products may give rise to health risks including phototoxicity, photosensitivity, and photosensitivity. Natural polysaccharides have attracted considerable interests due to diverse biological activities. Methods A novel polysaccharide isolated was purified and structurally characterized using chemical methods followed by HPLC, GLC-MS, as well as 1D and 2D NMR spectroscopy. The photoprotective effect of the EPS on UVB-induced damage was assessed in vitro using cultured keratinocytes and in vivo using C57BL/6 mouse models. Results The average molecular weight of the EPS was 5.48 × 106 Da, composed of glucose, mannose and galactose residues at a ratio of 2:2:1. The repeating units of the EPS were →3)-β-D-Glcp (1→3) [β-D-Galp (1→2)-α-D-Glcp (1→2)]-α-D-Manp (1→3)-α-D-Manp (1→. In cultured keratinocytes, the EPS reduced cytotoxicity and excessive ROS production induced by UVB irradiation. The EPS also exhibits an inhibitory effect on oxidative stress, inflammation, and collagen degradation found in the photodamage in mice. 1H NMR-based metabolomics analysis for skin suggested that the EPS partly reversed the shifts of metabolic profiles of the skin in UVB-exposed mice. Conclusion The EPS exhibits skin photoprotective effects through regulating oxidative stress both in vivo and in vitro. Our findings highlight that the EPS is a potential candidate in sunscreen formulations for an efficient solution to UVB radiation.